A Study on Workplace Violence Factors in Universiti Utara Malaysia - Hussain, Mohammad Ahmad Mohammad (2009)
The main purpose of this study is to examine is there any relationship between working environment, co-worker relationship, and management style and workplace violence in University Utara Malaysia. The dependent variable is workplace violence.The independent variables are working environment, co-worker relationship, and management style.This study is conducted quantitatively where data is collected through distribution of questionnaires to 102 respondents of employees of the managerial level and selected randomly in a public learning institution in Kedah. The data that have been collected were processed using SPSS (Statistical Package for Social Science) 16.0 software.The findings show that there is a positive significant relationship between working environment and the workplace violence, while the other factors, co-worker relationship and management style, shows no relationship with the workplace violence.